Vulnerability of invasive glioblastoma cells to lysosomal membrane destabilization - Vadim Le Joncour; Pauliina Filppu; Maija Hyvönen; Minna Holopainen; S Pauliina Turunen; Harri Sihto; Isabel Burghardt; Heikki Joensuu; Olli Tynninen; Juha Jääskeläinen; Michael Weller; Kaisa Lehti; et al. (EMBO Molecular Medicine)
Abstract The current clinical care of glioblastomas leaves behind invasive, radio‐ and chemo‐resistant cells. We recently identified mammary‐derived growth inhibitor (MDGI/FABP3) as a biomarker for invasive gliomas. Here, we demonstrate a novel function for MDGI in the maintenance of lysosomal membrane integrity, thus rendering invasive glioma cells unexpectedly vulnerable to lysosomal membrane destabilization. MDGI silencing impaired trafficking of polyunsaturated fatty acids into cells resulting in significant alterations in the lipid composition of lysosomal membranes, and subsequent death of the patient‐derived glioma cells via lysosomal membrane permeabilization (LMP). In a preclinical model, treatment of glioma‐bearing mice with an antihistaminergic LMP‐inducing drug efficiently eradicated invasive glioma cells and secondary tumours within the brain. This unexpected fragility of the aggressive infiltrating cells to LMP provides new opportunities for clinical interventions, such as re‐positioning of an established antihistamine drug, to eradicate the inoperable, invasive, and chemo‐resistant glioma cells from sustaining disease progression and recurrence.